Handbook of Hydroxyacetophenones: Preparation and Physical Properties - Martin, Robert; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
Hydroxyacetophenones constitute the starting material for a wide variety of syntheses in organic chemistry. They are versatile building blocks serving many different applications, such as specialty polymers, pharmaceuticals and fine chemicals. In this Handbook the diverse ways of obtaining over 3000 hydroxyacetophenones are described and their physico-chemical properties and spectroscopic data references are indicated. The Handbook is presented in dictionary style, with a logical classification of the ketones, making the information easily available for consultation. Ketones are classified methodically. They are thus easily accessible from three tables: the molecular formula index the chemical abstracts registry the usual names index. This completely revised and enlarged edition includes: 10 additional chapters compared with the previous edition which had just 2 chapters an additional 1500 ketones updated information for ~1200 ketone entries the addition of di- and polyketones approximately 3500 references. This Handbook is the reference on hydroxyacetophenones. It is a powerful synthesis tool for the researcher or industrial producers. Nowhere else are so many compounds covered or the physical properties and relevant syntheses provided. It provides a wide choice of hydroxyketones required to achieve syntheses based upon this range of intermediates.
Keywords: Chemistry; Organic chemistry; Chemistry; Organic Chemistry; Electronic books